Heritage or Heresy : the Public Interpretation of Archaeology and Culture in the Maya Riviera. - Walker, Cameron (Caribbean archaeology and ethnohistory., 2009)
How can we effectively interpret and present one culture to another without stereotypes or over-simplifications? What is the best way to present an authoritative version of a national heritage without also endangering ancient sites or being insensitive to the local customs, beliefs, and religious practices of the Indigenous peoples? This volume addresses the ongoing thrust in archaeology to take the next step after preserving the past: interpreting that past for the future. That future audience includes both local citizens and tourists who may have little background in archaeology, anthropology.